Gambaran Pengetahuan Orang Tua tentang Implementasi Toilet Training pada Anak Usia 4-5 Tahun di TK Arifah Desa Lassang Barat Polombangkeng Utara - Nur Rahmi; Kasmawati Kasmawati; Rudi Salam; Asrul Muarif (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
Toilet training is an effort to train children's habits in controlling urination and defecation activities in the correct and regular place. Apart from that, toilet training also teaches children to clean their own feces and put their pants back on independently without the help of others. Toilet training readiness in children can be influenced by parental motivation, the child's own readiness physically, psychologically and intellectually. The aim of this research is to determine the description of parents' knowledge about the implementation of toilet training for children aged 4-5 years in the Arifah kindergarten, West Lassang village, North Polombangkeng sub- district, Takalar district. The research method used was descriptive observational with a survey method. The research was carried out using a questionnaire sheet accompanied by a respondent's consent form. The results of the research conducted on 30 parents as respondents at the Arifah Kindergarten, West Lassang Village, North Polombangkeng District, Takalar Regency showed that that most respondents had good knowledge about implementing toilet training in children aged 4-5 years, namely 66.7%. Then those who have sufficient knowledge about the implementation of toilet training in children aged 4-5 years are 23.3% and those who have insufficient knowledge about the implementation of toilet training in children aged 4-5 years are 10%. It is hoped that future researchers can continue the research This is by developing variables from this research.